Conjoined nerve root in a patient with lumbar disc herniation accompanied by a lumbosacral spine anomaly: a case report - Hiroshi Kuroki; Takuya Nagai (Journal of Medical Case Reports, 2023)
Abstract Background A nerve root anomaly, typified by a conjoined nerve root, is a rare finding. Conjoined nerve root anomalies are easily missed even in preoperative advanced imaging modalities, which can be potentially troublesome during and after surgery. In this report, we present a case of conjoined right L5–S1 nerve root in a patient with lumbar disc herniation, accompanied by spina bifida occulta, which was undiagnosed on preoperative imaging studies. Case report A 55-year-old Asian (Japanese) woman presented with low back pain and right leg radiating pain due to lumbar disc herniation at the right L5/S1. Physical examination revealed a positive Lasègue sign and the range of the straight leg raising test was 20° on the right side. The right patellar tendon reflex was normal; however, the right ankle jerk reflex disappeared. Although no obvious hypoesthesia was noted, mild muscle weakness (4/5) was observed in the right leg on the manual muscle test. We planned the lumbar discectomy under a microscope. During surgery, the conjoined right L5–S1 nerve root, which was compressed by herniated nucleus pulposus, was encountered. Although it was very thick and less mobile, some pieces of herniated nucleus pulposus could be removed piece by piece from the axillary part. After sequential decompressive procedures, the tightness of the conjoined right L5–S1 nerve root decreased but its mobility did not improve much. The laterality of the thickness and exit angle of the conjoined right L5–S1 nerve root was retrospectively confirmed on T2 coronal magnetic resonance images and magnetic resonance neurography. Postoperatively, right leg pain was immediately alleviated and complete improvement of muscle weakness was achieved 1 week later (5/5). Conclusions Magnetic resonance neurography is extremely useful for the accurate diagnosis of anomalous nerve roots because of clear visualization of the neural tissue. Discectomy under a microscope, which enables magnified three-dimensional observation of the surgical field, must provide a valid and safe procedure to achieve not only secure resection of herniated discs but also adequate exposure of anomalous nerve roots.